Market reactions to climate news: Assessing industry portfolio performance - Lehtinen, Ilkka (2025)
Climate change is one of the biggest challenges today, and global warming has consequences for the whole economy. Climate-related news coverage can shift the attention to climate-related risks and impact investor decision-making. In recent years, different authors have documented stock market reactions to climate news. However, the climate risk exposures are different in each sector of the economy, and therefore, the stock market reactions can vary between industries. This study investigated whether the stock market reactions to climate news vary between climate risks and industries. In addition, the time variance of these effects was analyzed as the attention to climate-related risks has increased in recent decades. The stock market reactions were examined using daily industry portfolio returns, media-based climate risk indices, and common asset pricing factors from 2003 to 2024. The analysis was conducted using the climate risk variables together with a six-factor asset pricing model. The results showed that the stock market reactions were strongest for physical risk news and weakest for regulatory risk news. Both negative and positive reactions were observed, but the negative reactions were stronger. The negative reactions were strongest for brown industries. After the Paris Agreement, the stock market reactions decreased significantly in magnitude. Overall, the results suggest that before the Paris Agreement, investors were most sensitive to news concerning the direct consequences of global warming, and adverse climate coverage most severely impacted unsustainable industries. Furthermore, climate risks seem to be more accurately priced in the stock markets after the Paris Agreement.